2007
DOI: 10.1162/jiec.0.1110
|View full text |Cite
|
Sign up to set email alerts
|

?Uncovering? Industrial Symbiosis

Abstract: Since 1989, efforts to understand the nature of interfirm resource sharing in the form of industrial symbiosis and to replicate in a deliberate way what was largely self-organizing in Kalundborg, Denmark have followed many paths, some with much success and some with very little. This article provides a historical view of the motivations and means for pursuing industrial symbiosis-defined to include physical exchanges of materials, energy, water, and by-products among diversified clusters of firms. It finds tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
139
0
7

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(149 citation statements)
references
References 32 publications
2
139
0
7
Order By: Relevance
“…Industrial ecosystems have sprung up all over the world, mostly in regions with large‐scale, heavy industrial processes, such as Kwinana Industrial Area in Australia (Van Beers et al 2007; van Berkel 2004) and Rotterdam Harbor in the Netherlands (Baas and Boons 2004), but also around small‐scale agricultural practices, such as the Montfort Boys Town in Fiji (Zero Emissions Research and Initiatives 2005). In the United States, though more than a dozen eco‐industrial developments were planned, none materialized as idealized industrial ecosystems (Chertow 2007; Gibbs et al 2005). Many nascent industrial ecosystems are thought to exist, although they are not yet known to industrial ecologists.…”
Section: Introductionmentioning
confidence: 99%
“…Industrial ecosystems have sprung up all over the world, mostly in regions with large‐scale, heavy industrial processes, such as Kwinana Industrial Area in Australia (Van Beers et al 2007; van Berkel 2004) and Rotterdam Harbor in the Netherlands (Baas and Boons 2004), but also around small‐scale agricultural practices, such as the Montfort Boys Town in Fiji (Zero Emissions Research and Initiatives 2005). In the United States, though more than a dozen eco‐industrial developments were planned, none materialized as idealized industrial ecosystems (Chertow 2007; Gibbs et al 2005). Many nascent industrial ecosystems are thought to exist, although they are not yet known to industrial ecologists.…”
Section: Introductionmentioning
confidence: 99%
“…According to the US President's Council on Sustainable Development defi nition, "EIP is a community of businesses that cooperate with each other and with the local community to effi ciently share resources (information, materials, water, energy, infrastructure and natural habitat), leading to economic gains, gains in environmental quality, and equitable enhancement of human resources for the business and local community" (Chertow 2007 ). However, in a broader context, eco-production refers to manufacturing of a product which has a signifi cantly lower impact on the environment during its production, use, or disposal and is greener in comparison with other products in the same category or with similar functionality.…”
Section: Concept Of Eco-production Eip and Industrial Symbiosismentioning
confidence: 99%
“…Industrial symbiosis (IS) networks or symbiotic transactions refer to the exchanges in which at least three different entities are involved in exchanging at least two different resources (Chertow 2007 ) and/or bilateral exchanges including by-product synergy, green twinning and kernels, and utility sharing systems. Industrial symbiosis (IS) networks or symbiotic transactions refer to the exchanges in which at least three different entities are involved in exchanging at least two different resources (Chertow 2007 ) and/or bilateral exchanges including by-product synergy, green twinning and kernels, and utility sharing systems.…”
Section: Concept Of Eco-production Eip and Industrial Symbiosismentioning
confidence: 99%
“…In the past 5 years, however, a range of other industrial symbiosis examples have found their way into the literature, and there are currently at least some 50 regions globally that display interfirm collaboration with physical exchanges of materials, energy, and water for competitive and environmental benefit. This set of regions is most likely the tip of the iceberg, as collaborating companies may not necessarily label their initiatives as industrial symbiosis until an outsider does so (Chertow [2007] called this phenomenon uncovering ).…”
Section: Kalundborg + 20mentioning
confidence: 99%
“…The cooperation structures and networks of physical exchanges vary considerably (Chertow 2007; Van Beers et al 2007; Van Berkel et al 2009). Kalundborg was initially driven by the need to develop a new industrial water source for two anchor companies (an oil refinery and a power station).…”
Section: Kalundborg + 20mentioning
confidence: 99%